People, lakes and seashores: Studies from the Baltic Sea basin and adjacent areas in the early and Mid-Holocene. (1st April 2018) - Groß, Daniel; Zander, Annabell; Boethius, Adam; Dreibrodt, Stefan; Grøn, Ole; Hansson, Anton; Jessen, Catherine; Koivisto, Satu; Larsson, Lars; Lübke, Harald; Nilsson, Björn
Abstract: During the Early and Mid-Holocene significant changes in the ecology and socio-cultural spheres occurred around the Baltic Sea. Because of the underlying climatic changes and thus environmental alterations, the area was the scene for various cultural developments during the period under investigation. In the course of the melting of the glaciers at the end of the last Ice Age, isostatic and eustatic movements caused continual changes to the Baltic Sea basin. Changes in water level, however, affected not only the Early and Mid-Holocene coastlines, but also the whole Baltic Sea drainage system, including large lakes, rivers and watersheds in the hinterland were also dramatically impacted by these ecological changes. Prehistoric people were thus affected by changes in resource availability and reduction or enlargement of their territories, respectively. In order to evaluate the impact of changes in the water and land networks on the environment, resource availability, and human behaviour, and to reconstruct human responses to these changes, we pursue an interdisciplinary approach connecting environmental and archaeological research highlighted through different case studies. Highlights: Human adaptations to climate change from a multidisciplinary perspective. Same preconditions are not faced with the same coping mechanisms. New data from various case studies across the Baltic Sea basin.